Rimau Virtual Challenge Charity Programme raises money for Endowment Fund - Nor Salwana, Mohammad Idris (2021)
PEKAN, 22 August 2021 - Yayasan UMP organised the Rimau Virtual Challenge 2021 Charity Programme to raise money for the Mawaddah Residential College Endowment Fund and the Universiti Malaysia Pahang (UMP) endowment.